2018
DOI: 10.1186/s13045-018-0572-x
|View full text |Cite|
|
Sign up to set email alerts
|

A novel generation 1928zT2 CAR T cells induce remission in extramedullary relapse of acute lymphoblastic leukemia

Abstract: BackgroundAnti-CD19 chimeric antigen receptor (CAR) T cells have shown promise in the treatment of B cell acute lymphocytic leukemia (B-ALL). However, its efficacy in B-ALL patients with extramedullary involvement is limited due to poor responses and neurotoxicity. Here, we utilized a third generation of CAR T cell vector, which contains the Toll/interleukin-1 receptor (ITR) domain of Toll-like receptor 2 (TLR2), to generate 1928zT2 T cells targeting CD19, and evaluated the efficacy of 1928zT2 T cells in relap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
65
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 93 publications
(75 citation statements)
references
References 32 publications
3
65
0
Order By: Relevance
“…56,57 In 10 out of 11 patients with active disease, greater expansion (up to 40-fold) of third-generation CAR T cells compared to second-generation CAR T cells was seen, and third-generation CAR T cells remained detectable at higher levels up to 160 days postinfusion. 53 Despite promising preclinical results and greater proliferative potential in early clinical trials, the clinical benefits of combining costimulatory domains within third-generation CAR T cells are yet to be conclusively demonstrated. Considering the results of Cheng et al, 25 who reported no significant difference between two-second-generation (CD28 vs 4-1BB) CAR T cells co-infused in patients, Ramos et al 56 concluded that third-generation CAR T cell therapy may be effective in the eradication of minimal residual disease and lead to longer, more durable remissions.…”
Section: Combining Costimulatory Domainsmentioning
confidence: 99%
See 2 more Smart Citations
“…56,57 In 10 out of 11 patients with active disease, greater expansion (up to 40-fold) of third-generation CAR T cells compared to second-generation CAR T cells was seen, and third-generation CAR T cells remained detectable at higher levels up to 160 days postinfusion. 53 Despite promising preclinical results and greater proliferative potential in early clinical trials, the clinical benefits of combining costimulatory domains within third-generation CAR T cells are yet to be conclusively demonstrated. Considering the results of Cheng et al, 25 who reported no significant difference between two-second-generation (CD28 vs 4-1BB) CAR T cells co-infused in patients, Ramos et al 56 concluded that third-generation CAR T cell therapy may be effective in the eradication of minimal residual disease and lead to longer, more durable remissions.…”
Section: Combining Costimulatory Domainsmentioning
confidence: 99%
“…73 Moreover, increasing clinical experience in the early recognition and management of CRS and neurotoxicity is likely to reduce the incidence of severe toxicities, the early introduction of anti-IL-6 therapy and corticosteroids being associated with lower rates of life-threatening complications. 53,56,58 However, the number of recipients of third-generation CAR T cells in the published literature is low, and the results of additional trials, including some currently recruiting studies, will be needed to accurately assess toxicity risk (see Figure 4). CRS in particular often occurs during or near the peak of CAR T cell expansion.…”
Section: Safety Considerationsmentioning
confidence: 99%
See 1 more Smart Citation
“…In CD19-positive B cell malignancies, approximately 90% acute lymphoblastic leukemia (ALL) patients [1][2][3][4][5][6][7][8][9][10][11][12] and 70% lymphoma patients [13][14][15][16][17][18] can get remissions through CD19-specific CAR-T therapy. Encouragingly, two of the CD19-targeted CAR-T therapies, Kymriah and Yescarta, have been approved to treat relapsed/refractory (r/r) pediatric, young adult B cell ALL (B-ALL), and certain adult non-Hodgkin lymphomas (NHL) by the US Food and Drug Administration in 2017.…”
Section: Introductionmentioning
confidence: 99%
“…The exact mechanism of CAR-T induced neurotoxicity remains unclear but is thought to be at least partially driven by excessive cytokine production like CRS. The absence of CAR T-cells in cerebrospinal fluid in some cases of ICANS indicates an indirect mechanism for this process with diffusion of cytokines across the blood brain barrier being the most widely accepted mechanism of injury [25]. High levels of Granzyme B, which has previously been linked to neuronal injury, as well as IL-12 and IL-15 correlate with more severe ICANS [26].…”
Section: Cytokine Release Syndrome (Crs)mentioning
confidence: 99%